Analysis of Internal and External Wage gaps between Blacks and White Workers in the UK - Emeka Eze; Chukwuma Ogbonna; Edwin Udochukwu Nwachukwu; Joyce Chukwuma-Ogbonna (ESUT JOURNAL OF SOCIAL SCIENCES, 2026)
Both the internal wage gap within the Black ethnic minority and the impact of the intersection of gender and ethnicity on the external pay gap were investigated in this study.  According to the study's findings, black men make between 7% and 5% more money than black women, indicating a substantial wage disparity within the black ethnic group.  Additionally, we discover that Black workers, both male and female, have significant external wage gaps.